The Effect of Macroeconomics Factors on Happiness in Malaysia - Subramaniam, Vinothiny; Abdul Jalil, Norasibah (International Business Education Journal, 2025)
Many past studies concentrate on the relationship between macroeconomic factors and happiness. There is, however, very little empirical research on the same subject available in the case of Malaysia. Therefore, this study examines the effect of selected macroeconomic factors on levels of happiness in Malaysia. The time period considered in this study is from the year 2004 to 2021, and the data obtained come from various sources. To achieve the objective, data are analyzed by using the descriptive statistic tests and the multiple regression test. Output from multiple regression test provides an indication that the government expenditure (G) factor has a strong and positive association with happiness, while real GDP, on the other hand, recorded a negative relationship. This finding confirms the Easterlin paradox which made an assertion of a negative association between real GDP and happiness. Other than that, the positive relationship between government expenditures and happiness shows that increasing government spending over the years in schools, healthcare, road and infrastructure repairs, and social welfare has proven to improve happiness among Malaysians. The result for the inflation and unemployment test is positive and insignificant. These findings recommend that the Malaysian government should aim policies to promote people’s happiness by considering relevant and significant macroeconomic determinants of happiness.